The identity and distribution of Fiorinia phantasma (Cockerell & Robinson) Hemiptera: Coccomorpha: Diaspididae), with a new synonym - Watson, Gillian W.; Williams, Douglas J.; Miller, Douglass R. (Zootaxa, 2015)
The morphologies of Fiorinia phantasma (Cockerell & Robinson) (Hemiptera: Coccomorpha: Diaspididae) and F. coronata Williams & Watson are reviewed, and the name F. coronata is placed as a junior synonym of the name F. phantasma syn. n. The known geographical distribution and host range of F. phantasma is documented and discussed. An identification key to 12 of the 16 species of Fiorinia known from the Australasian, Nearctic and Neotropical Regions is provided.